Analysis of Labor Conditions and Health Indicators of Viticulture Workers in Bukhara Region - Azimovich, Berdiev Umidjon (American Journal of Biodiversity, 2025)
Current on the day village farm field, including viticulture network Uzbekistan Republic in the economy important place holds Viticulture in the field labor activity row dangerous and health for inconvenient characterized by factors. Physical heavy labor, high temperature and moisture, dusty air, pesticide and agrochemicals related to effects workers to your health negative impact shows. These factors labor productivity and to workforce stability directly impact does.